Phase diagram of the Potts Model with competing interactions - Ganikhodjaev, Nasir (American Institute of Physics, 2009)
We study the phase diagram for the Potts Model on a Cayley tree with competing nearest‐neighbor interaction J1 and next‐nearest‐neighbor interactions J2 and J3. To perform this study, an iterative scheme similar to that appearing in real space renormalization group frameworks is established. The phase diagram contains a modulated phase, as found for similar models on periodic lattices, and also new phase, namely, antiferromagnetic phase